Implementation of Islamic Economic Principles in Dairy Milk Transactions: Case Study Of Mining Village, Ponorogo - Diah Sohnya Pratika; Nur Kasanah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research focuses on the relationship between farmers and collectors in the milk distribution system in Desa Tambang, which shows an imbalance in bargaining power and a lack of transparency in the price determination process. The main problem found is the collectors' control over the distribution channel, so that farmers do not receive economic value in return for their labor. This research aims to explore these conditions through qualitative research methodology using the case study method. Data collection techniques were conducted through in-depth interviews, observation and documentation. The research findings show that the current distribution system is not fair and oriented towards social welfare. Based on John Rawls' theory of justice and Islamic economic principles, this research presents an alternative distribution system that is fair, transparent and inclusive. This alternative is expected to empower farmers through equitable partnerships and improve their welfare in a sustainable manner.